Investigations Of Seafloor Hydrothermal Mineralisation In Volcanic Arcs, Back Arcs And Continental Shelf Settings In SW Pacific And SE Asia - Timothy F. McConachy (International Marine Minerals Society, 2002)
Between April 2000 and April 2002, the Commonwealth Scientific and Industrial Research Organization (CSIRO) Division of Exploration and Mining has led 6 research expeditions totalling 160 days ship time in waters of Papua New Guinea, Vanuatu, Solomon Islands, Indonesia and Australia. Five expeditions were undertaken aboard the Australian research vessel Franklin following successful competitive research proposals, and the sixth used the Indonesian vessel Baruna Jaya VIII (see Table 1). In addition, two CSIRO participants joined JOIDES Resolution for the Ocean Drilling Program Leg 193 in the Manus Basin of PNG. The major scientific objective underpinning these expeditions was to locate and study present-day seafloor and sub-seafloor hydrothermal ore-forming activity in order to develop improved methods of exploring for ancient mineral deposits on land that originally formed by similar processes. The research has been supported financially by a number of Australian-based mineral companies, by Australian international aid agencies, and by appropriation funds from CSIRO, and was conducted in collaboration with researchers from Australia, Indonesia, Portugal, New Zealand, United States of America, South Korea, and the host nations. Building upon earlier successes in the 1986-1997 PACLARK-PACMANUS programs in the Woodlark and Manus Basins of PNG, we have sought to examine a wider range of geological settings in which ancient orebodies are inferred to have formed, including both volcanic and sediment-hosted environments. We have now visited volcanic arcs, fore-arc and triple-junction related submarine volcanoes, and back arc basins associated with convergent plate margins in the SW Pacific and SE Asia, as well as conceptual Mississippi-Valley-type targets associated with warm seeps at passive margins in the Great Australian Bight (see Figure 1). Surveys ranged from northern Sulawesi via far western Bismarck volcanic arc near PNG-Indonesia border, through the eastern Manus Basin and the Tabar-Lihir-Tanga-Feni chain in PNG, the western Solomon Islands festoon, the San Cristobal arc, parts of the Vitiaz arc, to the northern and southern New Hebrides arc in the Solomons and Vanuatu.